2021
DOI: 10.2214/ajr.20.24708
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Changes and Clinical Complications After Drug-Eluting Bead Versus Conventional Transarterial Chemoembolization for Unresectable Hepatocellular Carcinoma: Multicenter Study

Abstract: The publication of this Accepted Manuscript is provided to give early visibility to the contents of the article, which will undergo additional copyediting, typesetting, and review before it is published in its final form. During the production process, errors may be discovered that could affect the content of the Accepted Manuscript. All legal disclaimers that apply to the journal pertain. The reader is cautioned to consult the definitive version of record before relying on the contents of this document.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 42 publications
(51 reference statements)
2
21
0
Order By: Relevance
“…In this sense, DEB–TACE is different than conventional TACE, as the previously described two-part process (cTACE) is exchanged for a single-step modality (DEB–TACE). In randomized trials comparing cTACE and DEB–TACE, the major difference were less post-procedural pain and shorter hospital admission in DEB–TACE, this finding can be explained by the deeper penetration of chemoembolic material into the liver capsule and peritumoral portal venous system with cTACE [ 109 ].…”
Section: Mechanism Of Action Of Transarterial Therapiesmentioning
confidence: 99%
“…In this sense, DEB–TACE is different than conventional TACE, as the previously described two-part process (cTACE) is exchanged for a single-step modality (DEB–TACE). In randomized trials comparing cTACE and DEB–TACE, the major difference were less post-procedural pain and shorter hospital admission in DEB–TACE, this finding can be explained by the deeper penetration of chemoembolic material into the liver capsule and peritumoral portal venous system with cTACE [ 109 ].…”
Section: Mechanism Of Action Of Transarterial Therapiesmentioning
confidence: 99%
“…Recently, Zhang et al. showed that DEB-TACE caused more hepatobiliary injuries and severe abdominal pain ( 38 ).…”
Section: Tacementioning
confidence: 99%
“…Intrahepatic biloma and global hepatic damage associated with DEB-TACE has been hypothesized to result from the combination of chemotherapy-induced arteriosclerosis and ischemia. [8][9][10] Biliary strictures, particularly postsurgical anastomotic strictures, often present the diagnostic dilemma of whether the obstruction results from ischemia/scar or recurrent tumor.…”
Section: Cause Of Obstructionmentioning
confidence: 99%